2010
DOI: 10.1111/j.1439-0531.2010.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibrosarcoma in a Warmblood Mare

Abstract: This paper describes a case of uterine fibrosarcoma in an 18-year-old Warmblood mare. The mare had exhibited bloody fluid accumulation inside the uterus and vaginal haemorrhagic discharge since the previous foaling. The mare was euthanized, and on pathological examination, in addition to the uterine neoplasia, multiple metastases were found in the lungs, liver and spleen. The histological and immunohistochemical examination determined that the tumour was a fibrosarcoma. To our knowledge, this is the first pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…Primary fibrosarcomas of the intestine itself are extremely rare in dogs and other animal species (Goldschmidt and Hendrick 2002), and may originate anywhere in the body (Orr 1984;Mahler et al 2006;Speltz et al 2007;Govaere et al 2010). To the authors' knowledge, to date only one case has been reported in the veterinary literature, in which a tumour was described in a 17-year old Cocker Spaniel (Hurov 1962).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Primary fibrosarcomas of the intestine itself are extremely rare in dogs and other animal species (Goldschmidt and Hendrick 2002), and may originate anywhere in the body (Orr 1984;Mahler et al 2006;Speltz et al 2007;Govaere et al 2010). To the authors' knowledge, to date only one case has been reported in the veterinary literature, in which a tumour was described in a 17-year old Cocker Spaniel (Hurov 1962).…”
Section: Discussionmentioning
confidence: 91%
“…The skin and subcutis are the primary sites of occurrence of fibrosarcomas in dogs and other domestic animals (Goldschmidt and Hendrick 2002), but these can develop anywhere in the body such as the heart (Speltz et al 2007), liver (Gallati 1956), kidney (Brown et al 1975), urinary bladder (Olausson et al 2005), uterus (Govaere et al 2010), omentum (Rayner et al 2010), trachea (Mahler et al 2006) and, on rare occasions, in the mammary gland (Orr 1984). Primary malignant intestinal tumours are rare in dogs, and they may cause clinical signs of luminal obstruction, intestinal dysfunction and intestinal ulceration and/or perforation, resulting in septic peritonitis (Larock and Ginn 1997;Head et al 2002).…”
mentioning
confidence: 99%
“…In addition, an endometrial fibrosarcoma with invasion in the myometrium; tumor cell emboli in lymphatics; and metastases in lungs, liver, and spleen is described in an 18-year-old Warmblood mare [91]. Other published neoplasms with involvement of the endometrium are multicentric lymphosarcomas, i.e., T-cell lymphosarcoma in a 22-year-old pony mare [92] as well as B-cell lymphosarcomas in a 5-year-old Quarter horse mare [93] and an 8-year-old Thoroughbred mare [94].…”
Section: Endometrial Cancer: a Rare Disease In Maresmentioning
confidence: 99%
“…Leiomyoma, a benign neoplasia arising from the outer smooth muscle of the uterus, seems to be the most frequently occurring uterine tumor in mares (Van Camp, 1993). Several other tumors have sporadically been described affecting either the endometrium: fi broma (Estrada et al, 2008), fi brosarcoma (Govaere et al, 2011), adenocarcinoma (Gunson et al, 1980) and lymphosarcoma (Sweeney et al, 1991) or the myometrium: leiomyosarcoma (Lofstedt et al, 1987), fi broleiomyoma (Broome et al, 1992), and rhabdomyosarcoma (Torbeck et al, 1980). There is only one report on oviductal neoplasia (adenoma) in a mare (McEntee and Nielsen, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Benign masses which interfere with fertility may be removed. Malignant neoplasia are usually not treated since the prognosis is generally poor (Neufeld, 1973, Torbeck et al, 1980, Govaere et al, 2011.…”
Section: Introductionmentioning
confidence: 99%